Controle genético para a tolerância a geada em progênies de Eucalyptus urophylla - De Moraes, Cristiano Bueno; Tambarussi, Evandro Vagner; Gama, Lorena; Abilio, Fernanda Maria [UNESP]; Carignato, André [UNESP]; Zimback, Leo; De Paula, Rinaldo César [UNESP]; Mori, Edson [UNESP] (Instituto de Pesquisa e Estudos Florestais (IPEF), 2016)
This research aimed to study the genetic control of silvicultural traits in Eucalyptus urophylla progenies for frost tolerance. Three open-pollinated progeny tests were installed in a randomized blocks design, 150 progenies, four replications, six plants per plot. The tests were implemented in two contrasting regions for the occurrence of frost. In areas with frost occurrence the tests were implemented in the Eucatex (Itatinga/SP) and Palmasola (Palma Sola/SC) companies; for areas with rare frosts the trial was established in Experimental Station of Anhembi/SP. Plant height; diameter at breast height and wood volume at 12 and 24 months old were measured. The genetic variability in the population was high, the individual genetic variation coefficient ranging from 5.85% (ALT) to 22.58% (VOL) and the heritability in the narrow sense from 0.13 (ALT) to 0.77 (DAP and VOL), indicating a high potential for selection and breeding of the species for frost tolerance.
Genetic control for frost tolerance in Eucalyptus urophylla progenies
Keywords: Forest tree improvement; Frost; Genetic parameters; Progeny trial